5.24.17 Problems 1601 to 1700

Table 5.1047: Second or higher order ODE with non-constant coefficients

#

ODE

Mathematica

Maple

9874

\[ {}y^{\prime \prime }-a^{2} y = \frac {6 y}{x^{2}} \]

9875

\[ {}y^{\prime \prime }+n^{2} y = \frac {6 y}{x^{2}} \]

9876

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-\left (x^{2}+\frac {1}{4}\right ) y = 0 \]

9877

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (-9 a^{2}+4 x^{2}\right ) y}{4 a^{2}} = 0 \]

9878

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {25}{4}\right ) y = 0 \]

9879

\[ {}y^{\prime \prime }+q y^{\prime } = \frac {2 y}{x^{2}} \]

9880

\[ {}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0 \]

9881

\[ {}\left (2-x \right ) x^{2} y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

9882

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9883

\[ {}x y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

9884

\[ {}3 x y^{\prime \prime }-2 \left (3 x -1\right ) y^{\prime }+\left (3 x -2\right ) y = 0 \]

9885

\[ {}x \left (1+x \right ) y^{\prime \prime }-\left (x -1\right ) y^{\prime }+y = 0 \]

9886

\[ {}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0 \]

9887

\[ {}\left (x^{2}+2 x \right ) y^{\prime \prime }-2 \left (1+x \right ) y^{\prime }+2 y = 0 \]

9888

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9889

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9890

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

9891

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

9892

\[ {}\left (2 x -3\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9893

\[ {}y^{\prime \prime }-x y^{\prime }-3 y = 0 \]

9894

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9895

\[ {}y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

9896

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-y^{\prime }+y = 0 \]

9897

\[ {}x \left (1+x \right )^{2} y^{\prime \prime }+\left (-x^{2}+1\right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9898

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

9899

\[ {}x y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

9900

\[ {}x \left (x -1\right )^{2} y^{\prime \prime }-2 y = 0 \]

9901

\[ {}y^{\prime \prime }-2 x y^{\prime }+x^{2} y = 0 \]

9902

\[ {}x \left (-x^{2}+2\right ) y^{\prime \prime }-\left (x^{2}+4 x +2\right ) \left (\left (1-x \right ) y^{\prime }+y\right ) = 0 \]

9903

\[ {}x^{2} \left (1+x \right ) y^{\prime \prime }-\left (2 x +1\right ) \left (x y^{\prime }-y\right ) = 0 \]

9904

\[ {}2 \left (2-x \right ) x^{2} y^{\prime \prime }-x \left (4-x \right ) y^{\prime }+\left (3-x \right ) y = 0 \]

9905

\[ {}x^{2} \left (1-x \right ) y^{\prime \prime }+\left (5 x -4\right ) x y^{\prime }+\left (6-9 x \right ) y = 0 \]

9906

\[ {}x y^{\prime \prime }+\left (4 x^{2}+1\right ) y^{\prime }+4 x \left (x^{2}+1\right ) y = 0 \]

9907

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+12 y = 0 \]

9908

\[ {}x \left (x +2\right ) y^{\prime \prime }+2 \left (1+x \right ) y^{\prime }-2 y = 0 \]

9909

\[ {}x \left (x +2\right ) y^{\prime \prime }+\left (1+x \right ) y^{\prime }-4 y = 0 \]

9910

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9911

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9912

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

9913

\[ {}\left (x^{2}-2 x +10\right ) y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

9914

\[ {}y^{\prime \prime }-x y^{\prime }+2 y = 0 \]

9915

\[ {}\left (x +2\right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

9916

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-6 y = 0 \]

9917

\[ {}\left (x^{2}+2\right ) y^{\prime \prime }+3 x y^{\prime }-y = 0 \]

9918

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9919

\[ {}x^{2} y^{\prime \prime }+\left (\frac {5}{3} x +x^{2}\right ) y^{\prime }-\frac {y}{3} = 0 \]

9920

\[ {}2 x y^{\prime \prime }-y^{\prime }+2 y = 0 \]

9921

\[ {}2 x y^{\prime \prime }-\left (2 x +3\right ) y^{\prime }+y = 0 \]

9922

\[ {}2 x^{2} y^{\prime \prime }+3 x y^{\prime }+\left (2 x -1\right ) y = 0 \]

9923

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

9924

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9925

\[ {}x y^{\prime \prime }+\left (x -6\right ) y^{\prime }-3 y = 0 \]

9926

\[ {}x^{4} y^{\prime \prime }+\lambda y = 0 \]

9927

\[ {}4 x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}-25\right ) y = 0 \]

9928

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (36 x^{2}-\frac {1}{4}\right ) y = 0 \]

9929

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0 \]

9930

\[ {}x y^{\prime \prime }+3 y^{\prime }+x^{3} y = 0 \]

9931

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9932

\[ {}16 x^{2} y^{\prime \prime }+32 x y^{\prime }+\left (x^{4}-12\right ) y = 0 \]

9933

\[ {}y^{\prime \prime }-x^{2} y^{\prime }+x y = 0 \]

9934

\[ {}x y^{\prime \prime }-\left (x +2\right ) y^{\prime }+2 y = 0 \]

9935

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9936

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9937

\[ {}y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-2\right ) y = 0 \]

9938

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-2 x y^{\prime }+30 y = 0 \]

9939

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9940

\[ {}x y^{\prime \prime }+\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

9941

\[ {}2 x \left (x -1\right ) y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

9942

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 x y = 0 \]

9943

\[ {}x y^{\prime \prime }+\left (-2 x +2\right ) y^{\prime }+\left (x -2\right ) y = 0 \]

9944

\[ {}x^{2} y^{\prime \prime }+6 x y^{\prime }+\left (4 x^{2}+6\right ) y = 0 \]

9945

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9946

\[ {}x \left (1-x \right ) y^{\prime \prime }+\left (\frac {1}{2}+2 x \right ) y^{\prime }-2 y = 0 \]

9947

\[ {}4 \left (t^{2}-3 t +2\right ) y^{\prime \prime }-2 y^{\prime }+y = 0 \]

9948

\[ {}2 \left (t^{2}-5 t +6\right ) y^{\prime \prime }+\left (2 t -3\right ) y^{\prime }-8 y = 0 \]

9949

\[ {}3 t \left (t +1\right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9950

\[ {}x^{2} y^{\prime \prime }+\frac {\left (x +\frac {3}{4}\right ) y}{4} = 0 \]

9951

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\frac {\left (x^{2}-1\right ) y}{4} = 0 \]

9952

\[ {}x y^{\prime \prime }+\left (1-2 x \right ) y^{\prime }+\left (x -1\right ) y = 0 \]

9953

\[ {}x y^{\prime \prime }-\left (1+x \right ) y^{\prime }+y = 0 \]

9954

\[ {}x y^{\prime \prime }+3 y^{\prime }+4 x^{3} y = 0 \]

9955

\[ {}x^{2} \left (-x^{2}+1\right ) y^{\prime \prime }+2 x \left (-x^{2}+1\right ) y^{\prime }-2 y = 0 \]

9956

\[ {}2 x y^{\prime \prime }+\left (x -2\right ) y^{\prime }-y = 0 \]

9957

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9958

\[ {}y^{\prime \prime }+2 x^{2} y^{\prime }+\left (x^{4}+2 x -1\right ) y = 0 \]

9960

\[ {}u^{\prime \prime }-\left (2 x +1\right ) u^{\prime }+\left (x^{2}+x -1\right ) u = 0 \]

9961

\[ {}y^{\prime \prime }+2 y^{\prime }+\left (1+\frac {2}{\left (1+3 x \right )^{2}}\right ) y = 0 \]

9962

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9963

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}-\frac {2 y}{\left (1+x \right )^{2}} = 0 \]

9964

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9965

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9966

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9967

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9968

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9969

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9970

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9971

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9972

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9973

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]

9974

\[ {}y^{\prime \prime }-x y^{\prime }-x y = 0 \]